2019
DOI: 10.1155/2019/8013913
|View full text |Cite
|
Sign up to set email alerts
|

Clear-Cell Carcinoma of the Ovary with Bilateral Breast Metastases

Abstract: Ovarian clear-cell carcinoma is an uncommon subtype of epithelial ovarian carcinoma. It carries a generally poor prognosis because of its resistance to standard treatment and metastatic spread to vital organs. Metastasis to the breast is rare and bilateral breast metastasis is unreported. A 61-year-old white female with a 5-year status poststandard therapy for stage IC clear-cell ovarian carcinoma presented with widespread metastasis. Tissue analysis revealed ovarian cancer metastasis to the breasts bilaterall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Risk factors include early menarche, late menopause, nulliparity, infertility, BRCA1 and BRCA2 (breast cancer 1 and 2 gene) mutations, as well as Lynch syndrome. [3] In 1973, the World Health Organization (WHO) strictly defined ovarian clear cell carcinomas (OCCCs) as lesions characterized by clear cells growing in solid, tubular or glandular patterns with hobnail cells lining tubules and cysts. Subsequently, it was observed that Schiller's original descriptions actually included two distinct populations: a highly malignant germ cell tumor occurring in younger women, and another tumor of epithelial origin with a less aggressive phenotype,…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors include early menarche, late menopause, nulliparity, infertility, BRCA1 and BRCA2 (breast cancer 1 and 2 gene) mutations, as well as Lynch syndrome. [3] In 1973, the World Health Organization (WHO) strictly defined ovarian clear cell carcinomas (OCCCs) as lesions characterized by clear cells growing in solid, tubular or glandular patterns with hobnail cells lining tubules and cysts. Subsequently, it was observed that Schiller's original descriptions actually included two distinct populations: a highly malignant germ cell tumor occurring in younger women, and another tumor of epithelial origin with a less aggressive phenotype,…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is the fifth most frequent diagnosis of female malignancy and the second most common female gynecologic malignancy after breast cancer [1,2]. The 5-year prevalence is 213 cases per million with 2.1 percent deaths as per GLOBOCON 2020 data [3].…”
Section: Introductionmentioning
confidence: 99%